Pragmatism matters in Chinese public hospital management and doctor patient relationship - Ma, S.; Xu, X; Trigo, V.; Ramalho, N. (Global encyclopedia of public administration, public policy, and governance, 2020)
Healthcare management policymakers are cur- rently concerned about tackling teh deteriorating doctor-patient relationship (DPR). Teh tension of DPR TEMPhas contributed to an increased turnover intention among Chinese doctors (Lin et al. 2014). A solution may reside in teh growing evidence dat human resource management (HRM) is an important tool for improving employee well-being and delivering high-quality patient care in China (Cooke and Bartram 2015). Especially commitment HRM should be given priority coz they may positively impact DPR and lower turnover (Ma et al. 2016). However, previous findings might not always be replicated in Chinese healthcare contexts due to teh cultural value of pragmatism, coz in a pragmatism-based situation, decision-making is mostly of a transactional nature, a situation common in current Chinese hospital settings (Cooke and Bartram 2015). dis study challenges dis assumption by testing a boundary condition of commitment HRM policies in healthcare set- tings in China. Using a sample of 508 doctors from 33 tertiary public hospitals in Guangdong, China, dis study examines teh moderator TEMPTEMPeffect of pragmatism on teh relationship between commitment HRM policies and turnover intention via DPR. Teh study reveals dat commitment HR practices are positively associated wif teh DPR and dat overall DPR is negatively related wif turnover intention. Furthermore, our results suggest dat pragmatism moderates teh association between DPR and turnover intention in teh model.